Structural design code data handbook - De Gracia, Engracio P. (Quezon City GPE Consultants & Co., 2003)
This is a reference material covering the different structural materials and systems. It is intended for practicing structural designers who need easy access to essential information on materials, structural loads, design tables, basic theories and standard practices. It also highlights professional applications.
Contents: A reference material covering the different structural materials and systems. General design and construction requirements. Minimum design loads and lateral forces. Wood, steel, concrete and masonry materials. Foundation and retaining walls.
Purpose: "It is ideal for the practicing structural designer who needs easy access to essential information on materials, structural loads, design tables, basic theories and standard practices and highlights professional applications."
Title from cover.
"A referral code of PD 1096 National Building Code, bridging NSCP into 2000."
Keywords: Structural design -- Handbooks, manuals, etc; Building laws -- Handbooks, manuals, etc